2022
DOI: 10.1177/07334648221113500
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality Predicts Functional Disability in Older Adults with Low Back Pain: A Longitudinal Study

Abstract: Low back pain (LBP) and sleep quality are two very prevalent complaints in the older population. However, little is known about the prognostic relationship between sleep quality and disability in older adults with LBP. The aim of this study was to examine the association between sleep quality and disability in older adults with LBP. This was a longitudinal study over a 6-month period. Older adults with LBP in the last 12 weeks and who had preserved cognitive functions were recruited. The questionnaires used we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Many studies have reported an association between pain/function and sleep parameters, 9 10 but little is known about how OA, particularly knee pain, can affect sleep. Given these findings discussed above, we hypothesized that OA knee pain would be associated with poor sleep quality, increased daytime sleepiness, and symptoms of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported an association between pain/function and sleep parameters, 9 10 but little is known about how OA, particularly knee pain, can affect sleep. Given these findings discussed above, we hypothesized that OA knee pain would be associated with poor sleep quality, increased daytime sleepiness, and symptoms of depression.…”
Section: Introductionmentioning
confidence: 99%
“…3 4 There are some age-related physiological changes that can affect sleep without directly compromising physical, cognitive, and functional abilities 5 . However, sleep complaints are commonly accompanied by impairments in the performance of daytime activities 6 promoting, for example, fatigue, 7 daytime sleepiness, 8 musculoskeletal pain 9 10 and even a decrease in physical activity (PA). 8 There are several age-related factors that can affect sleep, 11 but there are also a range of factors not related to age that can influence sleep quality, such as alcohol 12 13 and tobacco consumption 14 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Daytime sleepiness, defined by having trouble staying awake during the day, is also associated with the increasing frequency of back pain ( Gustafsson et al, 2018 ). Although many observational studies have revealed a bidirectional relationship between sleep disturbances and LBP, the causal association are unclear due to the confounders ( Kelly et al, 2011 ; Goforth et al, 2014 ; Uhlig et al, 2018 ; Ho et al, 2019 ; Bilterys et al, 2021 ; Oliveira et al, 2022 ). A recent review focused on the association between sleep and spinal pain (including LBP) showed weak to moderate evidence of causality ( Van Looveren et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%